Covid-19 Disruption of Middle-Class Monthly Household Income and Budget - Gupta, Monika; Bansal, Shubhi (International Journal of Economics and Financial Issues, 2020)
Covid-19 has brought the life of every individual to a standstill. The middle class is in majority in India. The capable members in the family keep earning on monthly basis contributing to the Monthly Household Income (MHI) and keep on managing the activities as per household budget. But, the Covid-19 outbreak disrupted the way the middle class was managing household financial activities before the outbreak. Owing to prolonged lockdown all over the world, many of them have either lost their jobs or are on the verge of losing their jobs. It has really put a big question mark on the life of all the members in the house. Most of them are either paying EMIs of house or education loan, the basic necessities. It is completely dark everywhere. Moreover, shopping list of essentials has been changed. Masks, gloves sanitizers are occupying space above food and education. This is how Covid-19 has disrupted the monthly spending of the household. Cluster Analysis has been applied and two major clusters with ‘Highly Affected' and ‘Hardly Affected' households have been identified. No doubt, government and big corporate are coming up in front to support them in the hours of need. How long it will take to bring life back to normalcy-it is still difficult to predict. Keywords: Covid-19; Disruption; Middle-Class; MHI; Budget, India JEL Classifications: C38; D14; E24 DOI: https://doi.org/10.32479/ijefi.10675